2013
DOI: 10.1177/0300985813503569
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver Hemorrhagic Syndrome in the Backyard Chicken

Abstract: Fatty liver hemorrhagic syndrome, characterized by sudden death in overconditioned hens due to hepatic rupture and hemorrhage, is one of the leading noninfectious idiopathic causes of mortality in backyard chickens. Nutritional, genetic, environmental, and hormonal factors, or combinations of these, have been proposed yet not proven as the underlying cause. In an attempt to characterize the hepatic changes leading to the syndrome, this retrospective case study examined 76 backyard chickens that were diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 28 publications
8
78
0
1
Order By: Relevance
“…Necropsy findings in FLHS include abundant coelomic fat and an enlarged, tan to yellow, friable liver with hemorrhages. Another study revealed absence of hepatocellular lipidosis in 22% of the FLHS cases and mild hepatocellular lipidosis in 26% of the FLHS cases in the backyard birds (Trott et al, 2014).…”
Section: Noninfectious Diseasesmentioning
confidence: 94%
“…Necropsy findings in FLHS include abundant coelomic fat and an enlarged, tan to yellow, friable liver with hemorrhages. Another study revealed absence of hepatocellular lipidosis in 22% of the FLHS cases and mild hepatocellular lipidosis in 26% of the FLHS cases in the backyard birds (Trott et al, 2014).…”
Section: Noninfectious Diseasesmentioning
confidence: 94%
“…; Trott et al . ). It was reported that 74% of the total mortality in caged layers was due to FLHS in Queensland, Australia (Rozenboim et al .…”
Section: Introductionmentioning
confidence: 97%
“…Unfortunately, these characteristic gross findings could also indicate fatty liver or FLHS. Moreover, in the summer season, laying hens frequently suffer from fatty liver or FLHS, especially those reared in conventional battery cages [13-14,22-23] . In addition, other hepatic diseases, such as salmonellosis or inclusion body hepatitis by FAdV-4, could co-occur [24-25] , so careful diagnosis is needed so that other hepatic diseases are not overlooked.…”
Section: Discussionmentioning
confidence: 99%